182 NO ASSOCIATION BETWEEN CHANGES IN SYMPTOMS AND GASTRIC EMPTYING IN GASTROPARETIC PATIENTS TREATED WITH GASTRIC ELECTRICAL STIMULATION. (1st January 2006) - McCallum, R. W.; Lin, Z.; Sarosiek, I.; Forster, J.
Abstract : Aim: To investigate whether there is an association between gastric emptying rate and symptom improvement in gastroparetic patients treated with gastric electrical stimulation (GES). Methods: We retrospectively reviewed 63 gastroparetic patients (12 M, 51 F, mean age 41 years, range 21-66; 38 diabetic, 11 idiopathic, and 14 postsurgical) who had documented delayed gastric emptying of a solid meal and received GES therapy for at least 1 year. Patient characteristics, total symptom score (TSS) derived from 7 upper gastrointestinal symptom subscores (0-4) and 4-hour standardized gastric emptying test (GET) were evaluated at baseline and at 1 year of GES. Data are presented as mean (SE). Results: Of 63 patients, 14 had their GET normalized and 49 remained delayed GET at 1 year of GES (normal value at 2 hours < 60% and at 4 hours < 10% gastric retention). There was no difference in mean TSS reduction at 1 year between patients with normalized GE and delayed GE at 1 year (61% vs 59%). Nine of 14 (64%) patients with normalized GE and 31/50 (62%) with delayed GE at 1 year had a $ 50% reduction in TSS at 1 year (see Table below). Overall 33 patients did demonstrate decreased gastric retention while 30 patients had worsening of their GET. There were no differences in symptom improvement between the patients with a better GET and those with a worse GET at 1 year (see Table below). Conclusions: There is no association between changes in symptoms and gastric emptying in gastroparetic patients treated with GES, suggesting that the effect of GES is due to factors beyond gastric motility.